Fetal Ascites in a Cow: A Case Report - Waykule, S S; Koli, A B; Ramteke, S S; Patil, A D; Bhosale, Y B (Animal Reproduction Update, 2024)
A three and half year oldNon-Discript cow was presented to Veterinary Clinical Complex, COVAS, Udgir with the history of completion of gestation period and appearance of first water bag before two hours.Per-vaginal examination revealed that fetus is in posterior longitudinal presentation and fetal abdomen is fluid filled, larger in size, bulky, distended. The case was diagnosed as dystocia due to fetal ascites.Incision was given on fetal abdomen to drain the excessive fluid using Robert’s Guarded knife Following reduction, Dead male fetus was delivered successfully by two way coordinated traction.
Keywords: Cow; Dystocia; Fetal ascites; Robert’s Guarded Knife